Vilaprisan for treating uterine fibroids. (4th May 2018) - Melis, Gian Benedetto; Neri, Manuela; Piras, Bruno; Paoletti, Anna Maria; Ajossa, Silvia; Pilloni, Monica; Marotto, Maria Francesca; Corda, Valentina; Saba, Alessandra; Giancane, Elena; Mais, Valerio
ABSTRACT: Introduction : The medical strategy to antagonize myoma size and related-symptoms is to reduce estrogen and progesterone activity on myomas. This can be obtained with the GnRH agonist (GnRHa) or with compounds that antagonize progesterone stimulatory activity on myomas. Selective progesterone receptor modulators (SPRMs) bind progesterone receptor (PR), leading to both agonist and antagonist effects. The result of SPRMs's action is tissue-specific and it depends on the particular affinity and strength of each SPRM. Area covered : Ulipristal acetate (UPA) is the first SPRM registered for myoma treatment. UPA reduces heavy uterine bleeding within 7 days from the onset of treatment, whereas a longer time is required with GnRHa treatment. Vilaprisan is a novel powerful SPRM. Phase I and II studies give encouraging results on the efficacy of vilaprisan at different doses. Like other SPRMs, vilaprisan induces benign changes of endometrium (PR modulator-associated endometrial changes, PAECs). These disappear as treatment is discontinued. Unlike GnRHa treatment, neither UPA nor vilaprisan induce hypoestrogenism and associated symptoms. Phase III studies are ongoing to confirm efficacy and safety of vilaprisan in long-term treatment of symptomatic fibroids. Expert opinion : It is fundamental to underline the rapidity of action (only 3 days) in the control of myoma-related bleeding.